What is the integral of #(x+1)/(x(x^2+x-6))#?

Answer 1
#-1/6ln|x| - 2/15 ln|x+3| + 3/10 ln|x-2| + C#

Well, for one, we can factor the denominator:

#int(x+1)/(x(x^2 + x - 6))dx#
#int(x + 1)/(x(x+3)(x-2))dx -= int A/(x) + B/(x+3) + C/(x-2)dx#

Now we just have linear denominators, which is a fairly straightforward decomposition.

By achieving common denominators on the righthand side, we can equate the numerator to #x+1#. Therefore, multiply the top and bottom so that all the terms have the denominator #x(x^2 + x - 6)#.
#[A(x+3)(x-2) + B(x)(x-2) + C(x)(x+3)]/cancel(x(x+3)(x-2)) = (x+1)/cancel(x(x+3)(x-2))#

Simplify the left side so that it looks like a general polynomial. First, distribute:

#Ax^2 + Ax - 6A + Bx^2 - 2Bx + Cx^2 + 3Cx = x + 1#

Group together terms.

#Ax^2 + Bx^2 + Cx^2 + Ax - 2Bx + 3Cx - 6A = x + 1#
Now make sure you get it into this correct form, #bb(ax^2 + bx + c)#:
#ul((A + B + C))x^2 + ul((A - 2B + 3C))x + ul((-6A))#
#= ul(0)x^2 + ul(1)x + ul(1)#

This means we have a system of three equations:

#A + B + C = 0# #A - 2B + 3C = 1# #-6A = 1#
Clearly, #color(green)(A = -1/6)#, so the rest follows. Add the negative of the second equation to the first.
#" "A + B + C = 0# #- (A - 2B + 3C = 1)# #"------------------------------"# #" "" "" "3B - 2C = -1#
This gives #C = (-1 - 3B)/(-2) = 1/2 + 3/2B#, so from the first equation:
#-1/6 + B + 1/2 + 3/2B = 0#
#1/6 - 1/2 = 5/2B#
#=> color(green)(B = -2/15)#

Thus:

#color(green)(C) = 1/2 + 3/2*-2/15 = color(green)(3/10)#
You can verify #A#, #B#, and #C# by plugging them back into the system of equations. And so, we have:
#int(x + 1)/(x^3 + x^2 - 6x)dx#
#= -1/6int 1/(x)dx - 2/15 int 1/(x+3)dx + 3/10 int 1/(x-2)dx#
We know the integral of #1/u# to be #ln|u|#. Thus:
#=> color(blue)(int(x + 1)/(x^3 + x^2 - 6x)dx)#
#color(blue)(= -1/6ln|x| - 2/15 ln|x+3| + 3/10 ln|x-2| + C)#
Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer 2

To find the integral of ((x+1)/(x(x^2+x-6))), you first factor the denominator, then use partial fraction decomposition. Factoring the denominator gives (x(x^2+x-6) = x(x+3)(x-2)). The partial fraction decomposition of ((x+1)/(x(x^2+x-6))) is (A/x + B/(x+3) + C/(x-2)), where (A), (B), and (C) are constants. Solving for these constants yields (A = 1/2), (B = -1/4), and (C = 1/4). Therefore, the integral becomes ((1/2)\ln|x| - (1/4)\ln|x+3| + (1/4)\ln|x-2| + C), where (C) is the constant of integration.

Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer from HIX Tutor

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

Not the question you need?

Drag image here or click to upload

Or press Ctrl + V to paste
Answer Background
HIX Tutor
Solve ANY homework problem with a smart AI
  • 98% accuracy study help
  • Covers math, physics, chemistry, biology, and more
  • Step-by-step, in-depth guides
  • Readily available 24/7